Towards the development of a biobased economy in Europe and India. (18th August 2019) - Pant, Deepak; Misra, Shilpi; Nizami, Abdul-Sattar; Rehan, Mohammad; van Leeuwen, Rebecca; Tabacchioni, Silvia; Goel, Reeta; Sarma, Priyangshu; Bakker, Rob; Sharma, Neeta; Kwant, Kees; Diels, Ludo; et al.
Abstract: India has emerged as a key player with a high potential to develop a biomass and biobased economy due to its large geographic size and the massive amounts of agricultural and non agricultural biomass produced. India has joined hands with Europe to synchronize its efforts to create and facilitate the development of a biobased economy in this country. This paper aims to examine common research and development actions between the European Union (EU) and India to facilitate the development of these biobased economies. As a base, a thorough study has been performed considering the biomass potential and current status of the bioeconomy in both the EU and India based on the distillation of a series of 80 potential recommendations. The recommendations were grouped into four major categories: (1) biomass production, (2) by-products/waste, (3) biorefineries and (4) policy, market, and value-added products. A questionnaire was designed and distributed to key stakeholders belonging to: academia, industry, and policymakers in both India and the EU. A total of 231 responses were received and analyzed, based on the key recommendations made for the essential research and development topics that are of prime importance to develop biobased economies in both the EU and India. The findings of this study suggest recognizing the value-added contributions made by biobased products such as: food, feed, valuable materials and chemicals in both regions. It is important to reduce the overall process costs and minimize the environmental impacts of such a biobased economy.